Structure, properties, and preparation of perovskite-type compounds - Galasso, Francis S. (International series of monographs on solid state physics, 1969)
Structure, Properties and Preparation of Perovskite-Type Compounds, Volume 5 presents the various methods of preparing powders, single crystals, and thin films of perovskite-type compounds. This book discusses the structure of perovskite-type compounds and their properties. Organized into 11 chapters, this volume begins with an overview of the structure, properties, and preparation of perovskite-type compounds. This text then examines how X-ray diffraction can be used to determine unit cell data and to orient single crystals. Other chapters consider the effect of nuclear radiation on the prop.